Corrected adsorption rate model of activated carbon–ethanol pair by means of CFD simulation. (November 2016) - Jribi, Skander; Miyazaki, Takahiko; Saha, Bidyut Baran; Koyama, Shigeru; Maeda, Shinnosuke; Maruyama, Tomohiro
Highlights: CFD simulation of ethanol adsorption onto activated carbon was carried out. Fickian diffusion equation caused divergence in solving the mathematical model. Simulated adsorption uptake with isothermal LDF model was under-estimated. Corrected diffusion time constants of LDF model were extracted. Abstract: The adsorption rate is an important parameter for accurate performance estimation of adsorbent-refrigerant based adsorption cooling cycles. Here, we have investigated the response of two adsorption kinetics models of activated carbon–ethanol pair by means of CFD simulation. The isothermal assumption used in estimating the diffusion time constant of Fickian diffusion and linear driving force (LDF) models led to divergence and under-estimated adsorption uptakes, respectively. By including the simulated adsorbent temperature profile in fitting of LDF model to experimental data, we assessed the non-isothermal diffusion time constants which were 2.5 to 5 times higher than those evaluated previously with isothermal assumption. The goodness of fitting, evaluated with coefficient of determination ( R 2 ), improved and became higher than 0.95 from 0.73 initially. The developed non-isothermal LDF equation allows accurate heat and mass transfer simulations and performance optimization of large scale adsorption/desorption bed employing activated carbon-ethanol pair for adsorption cooling applications.